Pemantauan Pelaksanaan Pilkada 2024 Desa Sukamantri Kecamatan Karangtengah Kabupaten Cianjur: Dinamika dan Hasil Akhir - Zakhreva, Bunga Syauzan; Azaria, Haura Aimee; Nurmala, Sany (UIN Sunan Gunung Djati Bandung, 2025)
Pilkada is a democratic event to elect regional leaders who are competent and responsive to the needs of the community. This study aims to monitor the implementation of the 2024 Pilkada at TPS 2 Sukamantri Village, Karangtengah Subdistrict, Cianjur Regency, which includes all stages of the election, starting from the debate of candidate pairs (paslon), campaign, quiet period, voting, vote counting, to the recapitulation of vote results. The method used is a field study with a qualitative descriptive approach through direct observation at each stage of the election. The results showed that the three candidate pairs carried various visions, such as infrastructure development, education, and community economic development. The voter participation rate reached 74%, with 95.13% of valid votes. Despite some technical obstacles, such as a lack of understanding of the correct voting procedures, the electoral process in Karangtengah Sub-district, specifically at polling station 2 in Sukamantri Village, went smoothly and reflected the principles of healthy local democracy. This research also highlights the importance of the election committee's active role in maintaining a smooth process, as well as the need for better political education to increase public awareness and participation. Overall, high public participation and transparency of the electoral process are important factors that need to be improved to support the quality of democracy in the future.